Mechanical milling of tronoh silica sand nanoparticles using low speed ball milling process - Rizlan, M.Z. (2013)
Silica sand nanoparticles are widely used as filler, coating and reinforcer to increase materials strength and durability. The objective of the research is to design a new technique of converting Tronoh silica sand to silica sand nanoparticles by using ingenious combination of milling process and heating mechanism. Raw Tronoh silica sand was milled for 10 hours with heating process after every 2 hours of milling. The optimum parameters were first identified using Taguchi method of orthogonal array. By using the optimum parameters obtained, a lab-scale production has been done to test the ability for repetitive production of silica sand nanoparticles. Results from the lab-scale production were analyzed using particle size analyzer to obtain the particles size and size distribution. Particles size of less than 100 nm has been repeatedly achieved in this research. Findings from this research provide a simple and low cost alternative method of producing silica sand nanoparticles. Â© 2013 IEEE.